Abdominal-Pelvic Masses in Geriatrics: A Report about 02 Cases Explored at the Computed Tomography (CT) - Kouame N; Bakary YN; Manewa FS; Gaimou BP; Agoda AK; Ngoan Domoua AM; N'gbesso RD (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2016)
Abdominal-pelvic masses are often described in children and make dread malignancy. In adults or in the elderly, these masses are less documented and are rarely bulky and therefore rarely the cause of abdominal pelvic distension.We report 02 cases of abdominal-pelvic masses encountered in subjects aged 76 and 91 years explored on the computed tomography (CT) with the aim to emphasize the contribution of CT in the diagnosis of large abdominal-pelvic masses in the elderly in sub Saharan Africa. The examinations performed on multi-detector scanners of Toshiba and General Electric's brand were  done without and after iodinated contrast medium injection.This was in both cases 02 large fluid masses  with fine and regular walls measuring respectively 232 and 267mm in diameter.These masses that showed no malignancy was located in the left kidney for the case making suggest the diagnosis of  renal  cyst  type  2 of Bosniak (one thin partition).As for the second mass, it was a bladder distension on heterogeneous prostatic hypertrophy.The first patient underwent a cystectomy and a left security  nephrectomy while the second,by a simple procedure of catheterization has found the solution to his  mass.Large abdominal-pelvic masses in geriatrics are usually benign and of urologic origin.The scanner is a diagnostic support and allows the institution of a treatment that is sometimes banal as the setting of a urinary catheter.